Evaluation of User Experience on Digital Learning Platform Website Using System Usability Scale (Case Study: Pijar Mahir) - Emil R. Kaburuan, Joshua Laurence, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
User experience is one of the most important factors of an application. Pijar Mahir is a digital learning platform to increase job seekers skill. This research evaluates usability of pijarmahir’s website using system usability scale (SUS). SUS consists of ten statements as an evaluation instrument. Based on the results of SUS evaluation of the 101 respondents, Pijar Mahir’s website has an average SUS score of 72,67. Based on the result, 72,67 is in an “acceptable” category.